2016
DOI: 10.1542/peds.2016-1052
|View full text |Cite
|
Sign up to set email alerts
|

Parent Experience With False-Positive Newborn Screening Results for Cystic Fibrosis

Abstract: Although immediate distress was reported among mothers of FP infants, selected psychometric tools did not detect these concerns. The NBS center from which mothers were recruited minimizes delay between notification and confirmatory testing and ensures trained professionals are communicating results and facilitating follow-up. These factors may explain the presence of minimal psychosocial burden. The screening system reflected herein may be a model for NBS programs working to minimize FP-related psychosocial ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…Although ongoing efforts are required to support parents through the NBS journey, and system design is central to their experience, 9 we are reassured by the finding that no elevated use of primary care, mental health, or ED services was detected among mothers of FP infants. Because this is the first study in which researchers explore maternal health care use in the context of FP NBS results, and because the related evidence is equivocal, further research is warranted to generate a finer-grained understanding of the role of underlying health status provider practice patterns and parental psychosocial response in downstream health service use after newborn screening.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although ongoing efforts are required to support parents through the NBS journey, and system design is central to their experience, 9 we are reassured by the finding that no elevated use of primary care, mental health, or ED services was detected among mothers of FP infants. Because this is the first study in which researchers explore maternal health care use in the context of FP NBS results, and because the related evidence is equivocal, further research is warranted to generate a finer-grained understanding of the role of underlying health status provider practice patterns and parental psychosocial response in downstream health service use after newborn screening.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, it is possible that perceptions of uncertainty, worry about the long-term, or perceived infant vulnerability could explain increased use of respirology and genetics services. 9 However, these factors do not explain the increased rate of hospital admissions among FP infants. Because our follow-up window did not start until 3 months after the report of the screening result to allow for the confirmatory testing processes to take place for the majority, admissions are unlikely to be related to ongoing diagnostic testing.…”
Section: Discussionmentioning
confidence: 99%
“…For the component of the study reported herein, the full population of mothers of infants with true positive and inconclusive results seen at The Hospital for Sick Children in Toronto and a screen negative control sample were invited to participate during an 18-month period, via a modified Dillman design. 26,27 Because of the small number of inconclusive cases, we broadened the inclusion age, recruiting mothers retrospectively whose infants remained inconclusive with respect to diagnosis and were between the ages of 4 and 48 months or were seen at London Health Sciences Centre, a second regional NBS center in London, Ontario. The control group included a random sample of mothers of infants who screened negative for all conditions, identified through Newborn Screening Ontario.…”
Section: Samplementioning
confidence: 99%
“…The team-developed questionnaire was adapted from existing validated instruments used in infant/NBS research. [21][22][23][24][25][27][28][29] The core questionnaire was consistent across groups; content specific to the screen-positive experience was excluded from the version distributed to the screen-negative control group. We present overall scores on 3 well-established and validated psychosocial response measures: 27 (1) the state subscale of the State Trait Anxiety Inventory 28 as a measure of parental anxiety, (2) a modified version of the Parental Perceptions of Uncertainty in Illness Scale 29 as a measure of perceived uncertainty THE JOURNAL OF PEDIATRICS • www.jpeds.com Volume 184 related to childhood illness, and (3) the Child Vulnerability Scale 24 as a measure of maternal perception of infant vulnerability.…”
Section: Survey Of Mothersmentioning
confidence: 99%
“…This underlines the need for trained medical staff to manage parents’ fears and expectations when the disease, in an apparently asymptomatic newborn infant, needs to be defined in terms of phenotype severity or when a patient is heterozygous for one pathogenic variant and a pseudodeficiency variant. In order to improve the newborn screening process, we need to identify best practice for proper communication, as it has been shown that effective communication, including access to educational resources, can alleviate parental stress and minimise psychosocial burden after false‐positive newborn screening results .…”
Section: Introductionmentioning
confidence: 99%